Otolaryngology/head and neck region manifestations of Brucella. (14th January 2018) - Lazutkin, Anna; Korem, Maya; Weinberger, Jeffrey M.; Eliashar, Ron; Hirshoren, Nir
Abstract : Objectives/Hypothesis: Patients with Brucella infection present with nonspecific symptoms originating from different organs. In this study, we investigated the manifestations involving principally the otolaryngology/head and neck region. Study Design: Retrospective cohort chart review. Methods: A retrospective analysis of patients diagnosed with brucellosis in a tertiary medical center. Medical records of 55 patients treated for positive Brucella blood cultures between 2007 and 2016 were analyzed. Clinical manifestations localized to the otolaryngology/head and neck region were evaluated. Results: Most patients (78%) in our study group lived in rural areas. There was an almost equal gender distribution and a wide age range (2–77 years). Nonspecific symptoms, including fever (71%), fatigue (31%), weight loss (20%), and night sweats (32.7%) were the most common. Of the specific organ systems affected by Brucella, the osteoarthritic system was most commonly infected (45.5%). Three patients (5.5%) presented with predominantly localized otolaryngology/head and neck region symptoms, consisting of necrotic lymphadenopathy or a thyroid abscess. All patients underwent drainage procedures, and the diagnosis was confirmed by positive blood and pus cultures. Complete resolution was achieved with prolonged antibiotic treatment. Conclusions: Brucella infection should be suspected in patients with nonspecific constitutional symptoms associated with neck lymphadenopathy or thyroid abscess, especially in those living in rural areas. A high index of suspicion is mandatory for proper diagnosis and treatment. Formal drainage and prolonged antibiotic treatments are required. We strongly recommend simple drainage and not excision as the mainstay of surgical treatment. Level of Evidence: 4. Laryngoscope, 128:2056–2059, 2018